Meta-analysis: The effect of patient education on bowel preparation for colonoscopy - Chang, Chen-Wang; Shih, Shou-Chuan; Wang, Horng-Yuan; Chu, Cheng-Hsin; Wang, Tsang-En; Hung, Chien-Yuan; Shieh, Tze-Yu; Lin, Yang-Sheng; Chen, Ming-Jen (Endoscopy International Open, 2015)
Background and study aims: The proportion of outpatients with inadequate bowel preparation before colonoscopy is high owing to patient unawareness of its importance and poor adherence to instructions. This meta-analysis aimed to determine the effect of educational intervention on the quality of bowel preparation before colonoscopy.Patients and methods: A comprehensive literature review identified randomized controlled trials measuring the effect of educational intervention on the quality of bowel preparation. Two reviewers independently screened relevant articles, extracted data, and assessed the risk of bias. The primary outcome was the quality of each bowel preparation before colonoscopy, using a particular assessment scale. The secondary outcomes were polyp detection rates during the procedure and the need for a repeat colonoscopy due to incomplete examination.Results: Nine randomized controlled trials were included in this meta-analysis. In all, 2885 patients were enrolled, with 1458 receiving education and 1427 assigned to the control group. An educational intervention before colonoscopy significantly improved bowel preparation (relative risk [RR] = 1.22; 95 % confidence interval [CI], 1.10 – 1.36), however, no significant differences were identified in polyp detection rates (RR = 1.14; 95 %CI 0.87 – 1.51) or the need for repeat colonoscopy (RR = 0.52; 95 %CI 0.25 – 1.04) between the groups. Asymmetry in the appearance of the funnel plot and the result of Egger test (P < 0.001) suggested that publication bias existed.Conclusions: Evidence from these randomized controlled trials shows that a brief counseling session with patients before colonoscopy ensures better bowel preparation. However, evidence is insufficient to assess improvements in polyp detection rate and avoidance of a repeat colonoscopy. Despite these encouraging observations, this meta-analysis had some limitations, including potential publication bias and significant heterogeneity of the types of bowel purgatives. These results should be interpreted with caution.